Cellulose nanocrystals with different morphologies and chiral properties. (6th June 2018) - Korolovych, Volodymyr F.; Cherpak, Vladyslav; Nepal, Dhriti; Ng, Amy; Shaikh, Noor R.; Grant, Anise; Xiong, Rui; Bunning, Timothy J.; Tsukruk, Vladimir V.
Abstract: The study reports the morphology and optical properties of a variety of cellulose nanocrystals (CNC) obtained from different natural sources with different dimensions and composition. A library of CNCs components with different dimensions, sulfate contents, and crystallite sizes was prepared under identical hydrolysis conditions from five distinct sources representing traditional choices ranging from soft and hard wood pulps to microcrystalline cellulose. High-resolution atomic force microscopy, scanning electron microscopy, scanning transmission electron microscopy, and X-ray diffraction confirmed that all CNCs have a well-defined needle-like morphology with different aspect ratios and axi-asymmetric cross-sections. Varying the cellulose sources resulted in wide variability of the CNC dimensions, including length (120–210 nm), aspect ratio (30–70), height (2.9–3.6 nm), and width (6–11 nm). Specifically, the CNCs from microcrystalline sources have large cross-sectional dimensions and produce straight CNC bundles, but CNCs from wood pulps have small cross-sections and form twisted bundles of a few individual nanocrystals. Chemical composition and surface potentials were found to be less critical to the resulting chiral characteristics and structural colors while the CNCs with high aspect ratios form chiral films with large pitch values and thus longer wavelengths of selective reflection. Such flexible chiral CNC materials with controlled optical signature can be further considered for development of advanced materials for colorimetric sensors, tunable and active photonic materials, optical coatings, chiral inks and 3D printed photonic structures. Graphical abstract: Image 1 Highlights: High-resolution atomic force microscopy to probe morphology of CNCs from different sources. We explore the relationship between properties of CNCs and structure of their solid chiral phases. Local aggregation of CNCs, such as twisted bundles or parallel-packed straight nanocrystals are discussed.